Urban commons and cultural activities: governance and co-production processes in local communities - Colasanti, Nathalie; Frondizi, Rocco; Gulluscio, Carmela (Piccola Impresa / Small Business, 2025)
Purpose. The purpose of this paper is to reflect on cultural activity in cities, and on the contribution that urban commons can make to changing the urban cultural landscape. Design/methodology/approach. The analysis is set within the theoretical framework of the commons, and more precisely the urban commons: therefore, we will first carry out a review of the literature covering the key aspects of the framework. Then, we will introduce a descriptive case study aimed at providing an example of the contribution that urban commons can make to the definition of cultural activities in cities. Findings. We will find that communities managing urban commons, their values and objectives have great importance in defining the direction of cultural activities that can be carried out in such spaces; with this in mind, urban commons can make a valuable contribution to the cultural landscape of cities and neighborhood, and be part of a grassroots movement that shapes culture on the basis of social and collective needs. Practical and Social implications. Urban commons are often highly valued by local communities, as they become social and cultural hubs in their neighborhoods. At the same time, they often face opposition from local administration, mainly based on legal issues pertaining to the ownership of the spaces. Adopting a co-production approach to public value may allow such initiatives to flourish, with support from the public sector. Originality of the study. This paper links the fields of urban studies, with a specific focus on commons, with that of cultural activities, and takes into account a new, shared way of “making” culture in the city.